2017
DOI: 10.3389/fnmol.2017.00269
|View full text |Cite
|
Sign up to set email alerts
|

Loss of FMRP Impaired Hippocampal Long-Term Plasticity and Spatial Learning in Rats

Abstract: Fragile X syndrome (FXS) is a neurodevelopmental disorder caused by mutations in the FMR1 gene that inactivate expression of the gene product, the fragile X mental retardation 1 protein (FMRP). In this study, we used clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) technology to generate Fmr1 knockout (KO) rats by disruption of the fourth exon of the Fmr1 gene. Western blotting analysis confirmed that the FMRP was absent from the brains of the Fmr1 KO rats (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 71 publications
4
44
0
Order By: Relevance
“…A large spectrum of FXR-associated pathological changes found in mouse hippocampus include altered morphology of dendritic spines, behavioral changes, impairment of hippocampal synaptic plasticity and hippocampal-dependent memory tasks (reviewed in Bostrom et al, 2016 ). Furthemore, deficits in long-term memory in hippocampus and spatial learning were observed in rat models of FXR ( Tian et al, 2017 ). Many of FXR symptoms share a high degree of similarity to systemic changes and cognitive decline during normal aging which points to aging-related changes in the processes regulated by FMRP.…”
Section: Discussionmentioning
confidence: 99%
“…A large spectrum of FXR-associated pathological changes found in mouse hippocampus include altered morphology of dendritic spines, behavioral changes, impairment of hippocampal synaptic plasticity and hippocampal-dependent memory tasks (reviewed in Bostrom et al, 2016 ). Furthemore, deficits in long-term memory in hippocampus and spatial learning were observed in rat models of FXR ( Tian et al, 2017 ). Many of FXR symptoms share a high degree of similarity to systemic changes and cognitive decline during normal aging which points to aging-related changes in the processes regulated by FMRP.…”
Section: Discussionmentioning
confidence: 99%
“…The outlined data illustrate that the current FXS mouse models fail to mirror important genetic as well as behavioral aspects of FXS, probably due to the evolutionary distance of mice and men. To address this issue, two rat models were recently developed, Fmr1 KO 29 rats (Engineer et al, 2014 ; Till et al, 2015 ; Berzhanskaya et al, 2016b ; Kenkel et al, 2016 ) and Fmr1 exon4 KO rats (Tian et al, 2017 ). The investigations revealed that the new model animals indeed recapitulate many features of the murine model, including enhanced basal protein synthesis, exaggerated hippocampal mGluR-LTD, elevated dendritic spine densities and cortical hyper-excitability (Till et al, 2015 ; Berzhanskaya et al, 2016b ; Tian et al, 2017 ).…”
Section: From Mice To Menmentioning
confidence: 99%
“…To address this issue, two rat models were recently developed, Fmr1 KO 29 rats (Engineer et al, 2014 ; Till et al, 2015 ; Berzhanskaya et al, 2016b ; Kenkel et al, 2016 ) and Fmr1 exon4 KO rats (Tian et al, 2017 ). The investigations revealed that the new model animals indeed recapitulate many features of the murine model, including enhanced basal protein synthesis, exaggerated hippocampal mGluR-LTD, elevated dendritic spine densities and cortical hyper-excitability (Till et al, 2015 ; Berzhanskaya et al, 2016b ; Tian et al, 2017 ). However and much to a surprise, the rats neither reflect the behavioral phenotype of mice very well (Till et al, 2015 ), nor reproduce the symptoms of FXS patients any better than the murine model: although the animals demonstrated deficits in hippocampus-dependent learning (Till et al, 2015 ; Tian et al, 2017 ), they failed to display defects in spatial reference memory and reversal learning (Till et al, 2015 ), thereby contrasting not only the majority of data obtained from Fmr1 −/y mice (D’Hooge et al, 1997 ; Paradee et al, 1999 ; Van Dam et al, 2000 ; Baker et al, 2010 , reviewed in Kazdoba et al, 2014 ), but also the weak performance of FXS patients in tasks requiring the solution of new problems (Dykens et al, 1987 ; Maes et al, 1994 ; Loesch et al, 2004 ; Lewis et al, 2006 ; Van der Molen et al, 2010 ).…”
Section: From Mice To Menmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in SK channels have substantial implications for multiple other phenotypes at the cellular and behavioral level. Previous studies have found that FXS KOs have impaired LTP in CA1 hippocampus (Lauterborn et al, 2007;Lee et al, 2012;Tian et al, 2017). We suggest that this impairment might be partially due to elevated SK currents, which are known to shunt EPSPs and also to increase NMDA Mg 2+ block (Ngo-Anh et al, 2005).…”
Section: Sk Channel Over Expression May Underlie Previously Observed mentioning
confidence: 55%